Copolymerization of peroxy derivatives of dioxydiphenylpropane diglycidyl ether monomethacrylate with styrene - Iatsyshyn, Oksana; Bratychak, Michael; Shyshchak, Olena; Mitina, Nataliya; Zaichenko, Olexander (Publishing House of Lviv Polytechnic National University, 2015)
The copolymerization reaction of peroxy derivatives of dioxydiphenylpropane diglycidyl ether monomethacrylate with styrene has been studied at 333K in the medium of toluene using azo-bis-isobutyric acid dinitrile as an initiator at different molar ratio of the initial monomers. The reaction rates have been determined and copolymerization constants have been calculated. The structure of the synthesized copolymers was confirmed by chemical and IR-spectroscopic analyses. Вивчена реакція кополімеризації пероксидних похідних монометакрилату дигліциділового етеру диоксидифенілпропану із стиролом за температури 333 К у середовищі толуолу з використанням як ініціатор динітрилу азо-біс-ізомасляної кислоти та різного мольного співвідношення вихідних мономерів. Встановлені швидкості реакції та розраховані константи кополімеризації. Структура синтезованих кополімерів підтверджена хімічними та ІЧ-спектроскопічними методами дослідження.
Кополімеризація пероксидних похіднихмонометакрилату дигліциділового етеру диоксидифенілпропану із стиролом
Keywords: peroxide; monomethacrylic derivative of dioxydiphenylpropane diglycidyl ether; styrene; copolymerization; IR-spectroscopy; пероксид; монометакрилатна похідна дигліциділового етеру диоксидифенілпропану; стирол; кополімеризація; ІЧ-спектроскопія